A 3 1/2 year old girl with distal trisomy 19q defined by FISH. Issue 9 (September 1996) - James, C; Jauch, A; Robson, L; Watson, N; Smith, A
Abstract : A 3 1/2 year old girl was evaluated because of developmental delay. Short stature was evident with height between the 3rd and 10th centiles, while weight and head circumference were on the 50th centile. Dysmorphic features consisted of a high bossed forehead, pointed short ear lobes, small nose, bilateral convergent strabismus, left simian crease, a gap between the first and second toes bilaterally, mild clinodactyly, and a broad, barrel shaped thorax. Cytogenetic investigations showed an unbalanced karyotype, 46, XX, 10q+, which was de novo in origin. Fluorescence in situ hybridisation (FISH) using three library probes (from chromosomes 10, 19, and 19q) and a YAC probe (from 10q telomere) showed that the additional material on 10q was derived from chromosome 19q. The patient had an unbalanced translocation, 46, XX, -10, +der(10)t(10;19)(q26.3; q13.3), which resulted in distal trisomy 19q. Few other cases of proven distal trisomy 19q are available for comparison of clinical features.